Tumor cells with neuronal intermediate progenitor features define a subgroup of 1p/19q co‐deleted anaplastic gliomas. (28th October 2016) - Bielle, Franck; Ducray, François; Mokhtari, Karima; Dehais, Caroline; Adle‐Biassette, Homa; Carpentier, Catherine; Chanut, Anaïs; Polivka, Marc; Poggioli, Sylvie; Rosenberg, Shai; Giry, Marine; Marie, Yannick; et al.
Abstract: The integrated diagnosis of anaplastic oligodendroglioma, IDH mutant and 1p/19q co‐deleted, grade III (O3 id ) is a histomolecular entity that WHO 2016 classification distinguished from other diffuse gliomas by specific molecular alterations. In contrast, its cell portrait is less well known. The present study is focused on intertumor and intratumor, cell lineage‐oriented, heterogeneity in O3 id . Based on pathological, transcriptomic and immunophenotypic studies, a novel subgroup of newly diagnosed O3 id overexpressing neuronal intermediate progenitor (NIP) genes was identified. This NIP overexpression pattern in O3 id is associated with: (i) morphological and immunohistochemical similarities with embryonic subventricular zone, (ii) proliferating tumor cell subpopulation with NIP features including expression of INSM1 and no expression of SOX9, (iii) mutations in critical genes involved in NIP biology and, (iv) increased tumor necrosis. Interestingly, NIP tumor cell subpopulation increases in O3 id recurrence compared with paired newly diagnosed tumors. Our results, validated in an independent cohort, emphasize intertumor and intratumor heterogeneity in O3 id and identified a tumor cell subpopulation exhibiting NIP characteristics that is potentially critical in oncogenesis of O3 id . A better understanding of spatial and temporal intratumor cell heterogeneity in O3 id will open new therapeutic avenues overcoming resistance to current antitumor treatments.